Analysis of Fifth-Grade Students’ Mathematical Connection Ability in Understanding Fraction Concepts - Hidayat, Soleh; Sutarsih, Cicih (International Conference on Elementary Education, 2025)
This study aims to analyze the mathematical connection ability of fifth-grade elementary school students in understanding fraction concepts. Mathematical connection ability is one of the essential aspects that should be developed from the elementary education level, as it enables students to recognize relationships among mathematical concepts and apply them meaningfully in real-life situations. The research employed a qualitative descriptive method, with data collected through a mathematical connection ability test, observations, and interviews. The test instrument was developed based on three main indicators of mathematical connection ability proposed by the National Council of Teachers of Mathematics (NCTM), namely: (1) the ability to connect mathematical concepts, (2) the ability to connect multiple mathematical representations, and (3) the ability to connect mathematical concepts to real-life situations. The research subjects consisted of 30 fifth-grade students from a public elementary school in Garut Regency. The results indicate that the indicator of connecting mathematical concepts achieved the highest percentage at 68.7% (moderate category), followed by the indicator of connecting representations at 65.4% (moderate category), while the indicator of connecting mathematics to everyday life reached only 42.1% (low category). These findings suggest that students are generally able to identify relationships among mathematical concepts but still experience difficulties in applying these concepts to real-life contexts. Therefore, more in-depth instructional reinforcement is required to help students develop a more meaningful and applicable understanding of the mathematical concepts they learn.